Genetic divergence of HIV-1 B subtype in Italy over the years 2003–2016 and impact on CTL escape prevalence. Issue 1 (December 2018) - Alteri, Claudia; Fabeni, Lavinia; Scutari, Rossana; Berno, Giulia; Di Carlo, Domenico; Gori, Caterina; Bertoli, Ada; Vergori, Alessandra; Mastrorosa, Ilaria; Bellagamba, Rita; Mussini, Cristina; Colafigli, Manuela; et al.
Abstract HIV-1 is characterized by high genetic variability, with implications for spread, and immune-escape selection. Here, the genetic modification of HIV-1 B subtype over time was evaluated on 3, 328pol and 1, 152V3 sequences belonging to B subtype and collected from individuals diagnosed in Italy between 2003 and 2016. Sequences were analyzed for genetic-distance from consensus-B (Tajima-Nei), non-synonymous and synonymous rates (dN and dS), CTL escapes, and intra-host evolution over four time-spans (2003–2006, 2007–2009, 2010–2012, 2013–2016). Genetic-distance increased over time for bothpol andV3 sequences (P < 0.0001 and 0.0003). Similar results were obtained for dN and dS. Entropy-value significantly increased at 16pol and twoV3 amino acid positions. Seven of them were CTL escape positions (protease: 71; reverse-transcriptase: 35, 162, 177, 202, 207, 211). Sequences with ≥3 CTL escapes increased from 36.1% in 2003–2006 to 54.0% in 2013–2016 (P < 0.0001), and showed better intra-host adaptation than those containing ≤2 CTL escapes (intra-host evolution: 3.0 × 10−3 [2.9 × 10−3 –3.1 × 10−3 ] vs. 4.3 × 10−3 [4.0 × 10−3 –5.0 × 10−3 ], P[LRT] < 0.0001[21.09]). These data provide evidence of still ongoing modifications, involving CTL escape mutations, in circulating HIV-1 B subtype in Italy. These modifications might affect the process of HIV-1 adaptation to the host, as suggested by the slow intra-host evolution characterizing viruses with a high number of CTL escapes.